Aggressive driving: The role of aggression, driving anger, and self-efficacy - Čėsnienė, I.; Kašinska, A. (Psichologija, 2011)
According to the World Health Organization (2004), road traffic accidents are one of the ten leading causes of death. Many of these fatalities involve aggressive driving. P. Ellison-Potter et al. (2001) suggest that aggressive driving is any driving behaviour that intentionally endangers others psychologically, physically, or both. Examples of aggressive driving include behaviours such as excessive speeding, tailgating, horn honking, traffic weaving, profanity, obscene gestures, headlight flashing, etc. In order to understand this phenomenon, researchers have examined aggressive driving in terms of several levels of variables such as sociocultural, situational or personal (Valleries et al., 2005). Moreover, self-assessment of driving skills is a central dimension of driving activity. The evaluation of specific skills may be conceptualized by self-efficacy. Self-efficacy refers to individuals’ belief in their ability to accomplish specific goals (Bandura, 1995). The article reports the findings concerning the relationship between aggression, anger and self-efficacy among Lithuanian drivers. The sample consisted of 196 drivers (99 males, 97 females) aged 18 to 74 years. The Buss–Perry Aggression Questionnaire (Buss and Perry, 1992), the Driving Anger Scale (Deffenbacher et al., 1994), and the Adelaide Driving Self-efficacy Scale (George et al., 2007) were used in the study. Participants were administered also a questionnaire measuring a variety of demographical characteristics and driving-related factors. The results showed that more aggressive drivers tend to express the higher levels of driving anger than do less aggressive drivers. A negative relation between driving anger and driving self-efficacy was found. Further, the driving self-efficacy was higher in males than in females. Research findings indicate that there are gender differences in aggression, i.e. male drivers are more aggressive than female drivers. There are significant age differences in driver anger. In addition, high anger and aggression were related to unsafe driving behaviours. Seat-belt wearing tends to be less frequent among male drivers than among females. Aggression was found to be a predictor of crash-related outcomes. Finally, limitations of the study are discussed.